Is the nature of the demand regime relevant over the medium run? Some thoughts on the dynamic interaction between the exchange rate and demand regimes - Arslan Razmi (University of Massachusetts, Department of Economics, 2015)
Is growth in capitalist economies wage-led or profit-led? Empirical studies have found conflicting results for different countries and periods. Possible reasons may include differences in the monetary policy/exchange rate regimes across countries and between macro behavior in the short- and medium-runs. I theoretically explore these possibilities using a portfolio balance framework to keep track of asset stocks and wealth effects over time. With fixed exchange rates, the Central Bank's need to intervene in the asset market via official reserve transactions results in assigning a crucial role to the current account in constraining accumulation and output. The binding nature of this constraint vanishes with flexible exchange rates. The most important message that emerges is that, once we impose plausible constraints on dynamic behavior, factors other than the nature of the demand regime determine the effect of redistribution on utilization, income, and accumulation over the medium run. The demand regime loses relevance for reasons that vary with the exchange rate regime.
Keywords: F32; F43; E25; E42; E64; 330; Demand regime; wage-led growth; stagnationism; exhilarationism; neo-Kaleckian models; distribution; portfolio balance model; wealth effects